Preparation and spectroscopic investigations of hydroxyapatite-curcumin nanoparticles-loaded polylactic acid for biomedical application. Issue 1 (2nd January 2019) - Hezma, A. M.; Abdelrazzak, Abdelrazek B.; El-Bahy, Gamal S.
ABSTRACT: The main goal of this work is to fabricate a biocomposite material of hydroxyapatite (HA) and polylactic acid (PLA) loaded with different concentrations of curcumin for using in bone tissue scaffold engineering. PLA-HA-curcumin biocomposite was prepared via the precipitation method with PLA/HA ratio of 80/20 wt% and different ratios of curcumin. The structure and surface morphology of the prepared biocomposite were studied using Fourier Transform Infrared spectroscopy (FTIR), x-ray diffraction spectroscopy (XRD), transmission electron microscope (TEM) and scanning electron microscope (SEM). The bioactivity enhancement of the prepared HA-PLA biocomposite was examined after immersion in simulated body fluid (SBF) before and after addition of curcumin. Drug release of the HA-PLA biocomposite prepared with different concentrations of curcumin was studied in phosphate buffer solution. Our data confirm the nanostructure of the prepared HA-PLA biocomposite and show good miscibility and diffusion of curcumin inside the scaffold matrix. Furthermore, curcumin supplementation effectively enhanced the bioactivity of the HA-PLA biocomposite.